The Use of Blockchain Technology to Increase the Effectiveness of Supply Management Information for Logistic Enhancement (SMILE) based on Project Management Office in PT Telekomunikasi Indonesia - Liza Mahavianti Syamsuri; Eryda Listyaningrum (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The successful integration of blockchain technology into PT Telkom Indonesia's SMILE (Supply Management Information for Logistic Enhancement) system requires a structured and strategic approach. This study presents a comprehensive framework addressing technological, organizational, and regulatory aspects to ensure effective blockchain implementation. Recommendations include a phased implementation starting with pilot projects, integration of smart contracts to automate processes, and robust cybersecurity measures to safeguard data. Stakeholder engagement and training are emphasized to foster collaboration and acceptance, while adherence to regulatory compliance ensures alignment with legal requirements. The system's interoperability, platform selection, and sustainability considerations, such as energy-efficient consensus mechanisms, further enhance its functionality and environmental responsibility. Regular performance assessments using key performance indicators (KPIs) and partnerships with technology providers and academic institutions are suggested to drive continuous improvement and innovation. This framework positions PT Telkom Indonesia to optimize its supply chain operations and expand blockchain adoption across various organizational functions, setting a benchmark in the telecommunications industry.